2007
DOI: 10.1002/jso.20782
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to rehabilitation following surgery for primary breast cancer

Abstract: Surgery is a mainstay of primary breast cancer therapy. Alterations in surgical technique have reduced normal tissue injury, yet pain and functional compromise continue to occur following treatment. A tenuous evidence base bolstered by considerable expert opinion suggests that early intervention with conventional rehabilitative modalities can reduce surgery-associated pain and dysfunction. Barriers to the timely rehabilitation of functionally morbid sequelae are discussed at length in this article. Barriers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
178
1
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(194 citation statements)
references
References 63 publications
2
178
1
13
Order By: Relevance
“…These movements are described as abrupt and which stretch the upper limb 10,12,14 . The neuropathic pain is the factor responsible for increasing the complaint of pain when undertaking these movements, as it can lead to the development of the mechanical situation of restriction of shoulder movement 3,4,10,[12][13][14] . As the women in the sample studied were periodically undertaking exercises for rehabilitation of the range of movement of the upper limb, they were asked whether the pain increased when undertaking these exercises and 56.7% stated that it did not, while 23.3% reported that it sometimes increased and 20% said that the pain always increased with physical exercise.…”
Section: Pain In Women With Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These movements are described as abrupt and which stretch the upper limb 10,12,14 . The neuropathic pain is the factor responsible for increasing the complaint of pain when undertaking these movements, as it can lead to the development of the mechanical situation of restriction of shoulder movement 3,4,10,[12][13][14] . As the women in the sample studied were periodically undertaking exercises for rehabilitation of the range of movement of the upper limb, they were asked whether the pain increased when undertaking these exercises and 56.7% stated that it did not, while 23.3% reported that it sometimes increased and 20% said that the pain always increased with physical exercise.…”
Section: Pain In Women With Breast Cancermentioning
confidence: 99%
“…Knowledge about the pain relief measures is extremely important for the teams who work with these women 4,18 . Appropriate pain management must be implemented, avoiding self-treatment, since this can further compromise the symptom of pain in women with breast cancer 11,13 . …”
Section: Pain In Women With Breast Cancermentioning
confidence: 99%
“…Pathogenesis mechanisms have been proposed, such as endocrine, immunological, and inflammatory processes4. In addition, thyroid diseases, diabetes mellitus, Dupuytren contractures, breast cancer treatment, and autoimmune diseases have been associated with adhesive capsulitis in previous studies56789. Furthermore, patients diagnosed with myocardial infarctions and cerebral vascular diseases are reportedly at risk of adhesive capsulitis1011.…”
mentioning
confidence: 98%
“…As cirurgias por câncer de mama, bem como as terapias adjuvantes, podem resultar em algumas complicações físicas, dentre elas: infecção, necrose de pele, seroma, aderência e deiscência cicatriciais, limitação da amplitude de movimento (ADM) do ombro, cordão axilar, dor, alteração sensorial, lesão de nervos motor e/ou sensitivo, fraqueza muscular e linfedema [1][2][3][4][5][6][7] .…”
Section: Introductionunclassified
“…Vários são os recursos fisioterapêuticos utilizados no pós-operatório de câncer de mama, entre eles a cinesioterapia, a terapia manual e o complexo descongestivo fisioterápico 7,12,13 .…”
Section: Introductionunclassified